If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(-6 + 4r) = 90 (-6 * -3 + 4r * -3) = 90 (18 + -12r) = 90 Solving 18 + -12r = 90 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -12r = 90 + -18 Combine like terms: 18 + -18 = 0 0 + -12r = 90 + -18 -12r = 90 + -18 Combine like terms: 90 + -18 = 72 -12r = 72 Divide each side by '-12'. r = -6 Simplifying r = -6
| -8(2v+6)=-96 | | 5=-10+a | | 5=10+a | | R+6=25 | | 35-x^7=53+x^3 | | Whatisf(x)whenx=2.4 | | 90x=306 | | 2/3-4=-2 | | 8x-3(x+6)=x+14 | | 293-y=131 | | 75+7x=180 | | 2x+10+5x=3 | | 107+4x+15=180 | | 4x+5=107 | | 7y+7=4+2y | | 8(2x-5)+11x= | | X^2-xy-2y^2=(x+y)(x-2y) | | 5/12/3/16 | | 6x-8y=9x+10y-1z | | -3x/4x=21 | | -4.8/6.6 | | 6=2(w-7)-4w | | 5x+4(2x*10)=1 | | 15ab-4a+5b= | | 6x+7-3x=8x-13 | | 39=0.5(-12n+30) | | 4+3[6x-4(5+2x)]= | | 2x+26=146+2x+172 | | (4x+4y)x(4x-4y)= | | h=-16t^2+110t+6 | | (3z-1)/3 | | 3x-(-2-4x)=0 |